Nurse-patient communication while performing home dialysis: The patients' perceptions - Sadala, Maria Lúcia Araújo [UNESP]; Miranda, Marcelo Guimarães; Lorençon, Marisa; De Campos Pereira, Estela Pacheco (Wiley, 2010)
This study aimed at describing patients' perception of their communication with nurses when performing home dialysis. Data were collected from interviews guided by the question: What is communication like, between you and nurses, during home dialysis treatment? Results show participants' perception of treatment during home peritoneal dialysis [Continuous ambulatory peritoneal dialysis (CAPD)]; relationship with nurses and family and the effects of treatment on one's existence. Patients can be self-caring and they learn to value the autonomy in their own care. However, some are unable to assume the responsibility for self-care. It was discovered that the connotation of inspection that some participants attributed to the nurse's visits, led to an alienation from the education process in the CAPD education. Findings suggest that effective communication and the development of the relationship of a working partnership with patients is crucial. Improvement in the nurses' communication, aiming at adapting it to the characteristics, limitations and specific needs of each patient, is significant for achieving better outcomes. © 2010 European Dialysis and Transplant Nurses Association/European Renal Care Association.
Keywords: Communication; Home visit; Nursing care; Peritoneal dialysis; Phenomenology; adult; aged; attitude to health; continuous ambulatory peritoneal dialysis; female; human; interpersonal communication; male; middle aged; nephrology; nurse patient relationship; nursing; nursing discipline; patient education; professional practice; psychological aspect; Adult; Aged; Attitude to Health; Female; House Calls; Humans; Male; Middle Aged; Nephrology; Nurse-Patient Relations; Patient Education as Topic; Peritoneal Dialysis, Continuous Ambulatory; Specialties, Nursing